Introduction (Itinera, 2018)
This section gathers together the improved versions of the papers presented at the Benjaminian Colloquium «Art, Critique and Memory – Values and Historical Tensions in the Experience of the City», which took place at the Faculty for Social Sciences and Humanities of Universidade Nova de Lisboa on the 23rd of June 2016 as part of an ongoing research project – conducted by IFILNOVA’s group «Art, Critique and Aesthetic Experience».